2019
DOI: 10.1530/vb-18-0004
|View full text |Cite
|
Sign up to set email alerts
|

GPCR transactivation signalling in vascular smooth muscle cells: role of NADPH oxidases and reactive oxygen species

Abstract: The discovery and extension of G-protein-coupled receptor (GPCR) transactivation-dependent signalling has enormously broadened the GPCR signalling paradigm. GPCRs can transactivate protein tyrosine kinase receptors (PTKRs) and serine/threonine kinase receptors (S/TKRs), notably the epidermal growth factor receptor (EGFR) and transforming growth factor-β type 1 receptor (TGFBR1), respectively. Initial comprehensive mechanistic studies suggest that these two transactivation pathways are distinct. Currently, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 128 publications
0
14
0
Order By: Relevance
“…The engagement of receptor transactivation markedly expands the range of cellular responses attributable to the index cell surface, usually transmembrane, receptor. The current attributes of transactivation-dependent signalling encompass GPCR transactivation of kinase receptors [25,49,[59][60][61]. Mechanistic studies of GPCR transactivation-dependent signalling define a concrete signalling pathway [23,24,32,49].…”
Section: Discussionmentioning
confidence: 99%
“…The engagement of receptor transactivation markedly expands the range of cellular responses attributable to the index cell surface, usually transmembrane, receptor. The current attributes of transactivation-dependent signalling encompass GPCR transactivation of kinase receptors [25,49,[59][60][61]. Mechanistic studies of GPCR transactivation-dependent signalling define a concrete signalling pathway [23,24,32,49].…”
Section: Discussionmentioning
confidence: 99%
“…G protein-coupled receptors (GPCR) can signal via transactivation of protein tyrosine kinase (PTK) receptors [18] and protein serine (Ser)/threonine (Thr) kinase (PS/TK) receptors, specifically the TGFBR1 [4,[19][20][21][22]. Our lab has led the work in defining the mechanisms of GPCR transactivation of TGFBR1 [21,23]. We have shown that GPCRs promote cytoskeletal rearrangement that activates Rho GTPases and its downstream substrate Rho-associated protein kinase (ROCK) leading to integrin activation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that an alternative signaling pathway is critical for a variety of biological responses. The cross-communication between heterologous signaling systems and protein tyrosine kinases (PTKs), such as c-Src, epidermal growth factor receptor (EGFR), or platelet-derived growth factor receptor (PDGFR), is involved in various cell types, which can activate downstream signaling pathways such as the PI3K/Akt cascade [ 44 , 45 ]. Previous studies have demonstrated that the transactivation of EGFR or PDGFR is involved in proinflammatory cytokines (e.g., IL-1β) and induced several inflammatory mediators, such as MMPs in rat astrocytes [ 19 ] and human keratinocytes [ 46 ].…”
Section: Discussionmentioning
confidence: 99%